Reactivation and Mutation of Newly Discovered WU, KI, and Merkel Cell Carcinoma Polyomaviruses in Immunosuppressed Individuals - Sharp, Colin P.; Päivi, Norja; Anthony, Iain; Bell, Jeanne E.; Simmonds, Peter (The Journal of infectious diseases, 2009)
Background.Infection with the human polyomaviruses BK (BKV) and JC (JCV) is almost ubiquitous, asymptomatic, and lifelong. However, reactivation during immunosuppression, associated with mutations in the transcriptional control region (TCR) that up-regulates viral replication, can cause life-threatening disease. In this study, we investigated whether the recently discovered WU and KI polyomaviruses (WUPyV and KIPyV) and Merkel cell polyomavirus (MCPyV) could, like BKV and JCV, persist, mutate, and reactivate in immunodeficient subjects. Methods. Autopsy samples of lymphoid tissue from 42 AIDS-immunosuppressed subjects and 55 control samples were screened by polymerase chain reaction for all 5 polyomaviruses. TCR sequences from KIPyV and WUPyV recovered from both immunosuppressed and nonimmunosuppressed subjects were compared. Results.Combined polyomavirus detection frequencies were much higher for the immunosuppressed group, compared with the nonimmunosuppressed group (35.7% vs. 3.6%), with viral loads in lymphoid tissues ranging from ≤8.4 × 105 to >1.5 × 105 viral genome copies per 106 cells. MCPyV was recovered from only 1 HIV-negative study subject. TCR sequences from reactivated WUPyV and KIPyV variants showed a number of point mutations and insertions that were absent in viruses recovered from respiratory tract specimens obtained from nonimmunosuppressed subjects. Conclusions.KIPyV and WUPyV show reactivation frequencies comparable to those of BKV and JCV during immunosuppression. TCR changes that potentially lead to transcriptional dysregulation may have pathogenic consequences equivalent in severity to those observed for JCV and BKV.